Colonial Abuse and Environmental Displacement in Tarar’s Sorrows of Sarasvati - Akram, Muhammad; Shaheen, Aamer; Qamar, Sadia (Annals of Human and Social Sciences, 2023)
Humans, animals, plants and land are essential portion of environment. This paper presents colonial abuse upon different elements of colonized environment. Colonial abuse leads to environmental displacement in the form of escape, migration and elimination. Environmental displacement refers to the phenomenon where individuals or groups are compelled to migrate as their environmental conditions have become uninhabitable or unsustainable because of colonial violence. Employing a postcolonial eco-critical lens to analyze the environmental displacement and colonial abuse, the paper delves into the intricate interplay between human actions and ecological consequences in Mustansar Hussain Tarar’s novel Sorrows of Sarasvati: The Lost River (2021). Postcolonial eco-criticism is a theoretical framework that examines the representation of nature, environment, and ecology in literature within the context of post-colonial literature. Tarar’s novel depicts environmental challenges faced by the human and non-human entities, entangled with the legacy of colonialism. The paper specifically analyzes the contending environmental issues in postcolonial literature drawing from the theoretical underpinnings of Huggan and Tiffin’s concept of ‘Green Postcolonialism’ (2007) and emphasizes the need to integrate environmental concerns into postcolonial studies. Tarar’s novel generates eco-consciousness by taking the readers deep into the mystery of history of ancient civilization that resembles modern day Pakistan’s environmental position in many ways. In the tapestry of history, colonial invasion has been the main reason of devastation of indigenous people, native land, and local flora and fauna.